Melatonin Supplementation During In Vitro Maturation and Development Supports the Development of Porcine Embryos. Issue 6 (22nd September 2015) - Do, LTK; Shibata, Y; Taniguchi, M; Nii, M; Nguyen, TV; Tanihara, F; Takagi, M; Otoi, T
Contents: Melatonin has been reported to improve the in vitro development of embryos in some species. This study was conducted to investigate the effect of melatonin supplementation during in vitro maturation (IVM) and development culture on the development and quality of porcine embryos. In the first experiment, when the in vitro fertilized embryos were cultured with different concentrations of melatonin (0, 10, 25 and 50 ng/ml) for 8 days, the blastocyst formation rate of embryos cultured with 25 ng/ml melatonin (10.7%) was significantly increased (p < 0.05) compared to the control embryos cultured without melatonin (4.2%). The proportion of DNA‐fragmented nuclei in blastocysts derived from embryos cultured with 50 ng/ml melatonin was significantly lower (p < 0.05) than that of embryos cultured without melatonin (2.1% vs 7.2%). In the second experiment, when oocytes were cultured in the maturation medium supplemented with different concentrations of melatonin (0, 10, 25 and 50 ng/ml), fertilized and then cultured with 25 ng/ml melatonin for 8 days, there were no significant differences in the rates of cleavage and blastocyst formation among the groups. However, the proportions (2.7–5.4%) of DNA‐fragmented nuclei in blastocysts derived from oocytes matured with melatonin were significantly decreased (p < 0.05) compared to those (8.9%) from oocytes matured without melatonin, irrespective of the concentration of melatonin. Our results suggest that supplementation of the culture media with melatonin (25 ng/ml) during IVM and development has beneficial effects on the developmental competence and quality of porcine embryos.